Housing price in Singapore : determinants and future trends. - Goh, Suet Feng. (2008)
In view of the serious fluctuations in property prices in Singapore, our paper attempts to model the movements in housing prices in both the private and public housing markets. A simultaneous approach is adopted, incorporating the impacts of market variables, government anti-speculative policy, 1997 Asian Financial Crisis and property bubble.